Automated repair of mobile friendly problems in web pages - Mahajan, Sonai; Abolhassani, Negarsadat; McMinn, Phil; Halfond, William G. J. (2018 IEEE/ACM 40th International Conference on Software Engineering (ICSE), 2018)
Mobile devices have become a primary means of accessing the Internet. Unfortunately, many websites are not designed to be mobile friendly. This results in problems such as unreadable text, cluttered navigation, and content overflowing a device's viewport; all of which can lead to a frustrating and poor user experience. Existing techniques are limited in helping developers repair these mobile friendly problems. To address this limitation of prior work, we designed a novel automated approach for repairing mobile friendly problems in web pages. Our empirical evaluation showed that our approach was able to successfully resolve mobile friendly problems in 95% of the evaluation subjects. In a user study, participants preferred our repaired versions of the subjects and also considered the repaired pages to be more readable than the originals.